Sejarah Gaya Berbusana Perempuan Kota Jambi Tahun 1900 – 1970 - Emillia Emillia; Irhas Fansuri Mursal (Jurnal Siginjai, 2021)
This research is about the history of women's fashion style in Jambi in the 1900s - 1970s. Aims to add to the repertoire of writing about the history of gender and historical fashion in Jambi. This study describes how women's fashion style travels in Jambi City, as well as the influence of the entry of modernity and the impact it has on women's clothing styles in Jambi City. This research uses the historical method which has 4 stages, namely heuristics, source criticism, interpretation, and historiography. Kebaya clothing is a clothing that is often used in the daily life of women in the city of Jambi. But along with the times and culture, it began to shift with the presence of clothing from western countries such as dresses, mini skirts and midi skirts that showed the feminine side and also became a trend, especially for urban teenagers. The 1970s was a decade that was quite influential in the fashion sector in Indonesia, because this yearfashion designers began to appear and in Indonesia experienced freedom in dressing. For Jambi, this year is the year Jambi City women started wearing pants as their daily clothing. However, it does not make the existence of the kebaya and clothes brackets disappear.